The Analysis of Short Story Translation Errors (A Case Study of Types and Causes) - Syahrir Syahrir; St Hartina (Institut Agama Islam Negeri Palopo, 2021)
Translation of short stories as a literary work has become a trend lately because the short story provides entertainment and education for the readers. However, the translation process has been complicated because translators must be able to convey the message without changing the purposes of a source language. The preliminary observation discovered numerous errors made by students when they translate Indonesian short stories into English. Thus, this study aims to analyze the types and causes of translation errors in translating the short story. The descriptive qualitative approach is applied in document analysis. Data collection was carried out through translation tests and interviews. Then, the collected data were classified and analyzed by using Mathieu's (200 translations issues' theory (2003). The results discovered that the types of translation errors were a number of linguistic issues including grammatical issues, lexical choices, rhetorical problems, pragmatic problems, and cultural issues. The errors made were caused by the lack of vocabularies, misinterpretation of an idiomatic expression, figurative language, and implicit meaning, dissimilarities among cultural references and terms, the influence of the first language, and misunderstanding of English structure rules.